Hemoglobin I from Lucina pectinata on Collagen Scaffold: A Prospective Hydrogen Sulfide Scavenger - Jennifer Vargas Santiago; Anibal Quintana Cheeseborough; Juan López-Garriga (Journal of Chemistry)
Hydrogen sulfide (H2S), independently of being a toxic gas with a characteristic smell of rotten eggs, is a crucial signaling molecule with significant physiological functions. Given the rapid diffusivity of the gas, it is a challenge to develop robust sensors and biomarkers to quantify free or bound H2S. In addition, there is the need to further develop a robust biosystem to efficiently trap or scavenge H2S from different producing environments. The work presented here uses recombinant met-aquo rHbI (rHbI-H2O) immobilization techniques on collagen to determine its ability to bind H2S due to its high affinity (1.24×108 M-1). The hemeprotein will function as a scavenger on this scaffold system. UV-Vis absorption and UV-Vis diffuse reflectance (%R) spectroscopy of rHbI-H2O and rHbI-sulfide (rHbI-H2S) complex in solution and collagen scaffold demonstrated that the heme chromophore retains its reactivity and properties. UV-Vis diffuse reflectance measurements, transformed using the Kubelka-Munk function (K-M function), show a linear correlation (R2=0.9987 and 0.9916) of rHbI-H2O and rHbI-H2S within concentrations from 1 μM to 35 μM for derivatives. The extraordinary affinity of rHbI-H2O for H2S suggests recombinant met-aquo HbI in a collagen scaffold is an excellent scavenger moiety for hydrogen sulfide. These findings give insight into H2S trapping using the rHbI-H2O-collagen scaffold, where the rHbI-H2S concentration can be determined. Future pathways are to work toward the development of a met-aquo rHbI collagen solution capable of being printed as single drops on polymer, cotton or chromatographic paper. Upon exposure of these matrixes to H2S, the rHbI-H2S complex is formed and its concentration determined using UV-Vis diffuse reflectance technique.